Genetic identification against traffic in human beings. Issue 1 (21st August 2020) - Lorente, Jose A.; Saiz, Maria; Haarkötter, Christian; Robles‐Fernandez, Inmaculada; Alvarez‐Cubero, Maria J.; Galvez, Xiomara; Martinez‐Gonzalez, Luis J.; Lorente‐Remon, Begona; Alvarez, Juan C.
Abstract: The trafficking of human beings is one of the most heinous crimes on earth. Shamefully, human trafficking remains a lucrative business in 2020, just as it was thousands of years ago. The estimated astonishing number of victims would most likely surprise nonexperts. The prosecution of human trafficking is often difficult and requires the identification of victims. The fields of forensic anthropology and forensic odontology are of the highest value for this purpose. Forensic genetics is also of interest and can be applied not only to solving crimes but also to preventing them. At the University of Granada, we aim to pioneer the application of these technologies to both solve and prevent human trafficking. In 1999, we introduced the first national missing persons genetic identification program, the Spanish Phoenix Program; in 2004, we created and launched DNA‐PROKIDS, designed to deter child trafficking; and in 2016, we created DNA‐ProORGAN, a program that is currently being developed to identify transplanted organs, by obtaining DNA samples from the donor, the transplanted organ, and the recipient, to track transplants and identify illegal activities. Several tasks remain, despite existing technological advances and international cooperation. National missing persons databases must be enlarged, and new ones must be created, to facilitate the generation of reliable data. Specific legislation, at the national level, can be enacted to support database development and promote international interactions. These advances would help solve crimes and prevent them, representing the primary challenge faced by forensic science community in the 21st century. This article is categorized under: Forensic Biology > DNA Databases and Biometrics Abstract : The DNA‐PROKIDS logo is registered under my name (Jose A. Lorente) and belongs to the humanitarian program run by the (my) University of Granada under my direction. We have all the right‐s to use it.